Prevalence of antibodies to human papillomavirus (HPV) type 16 virus-like particles in relation to cervical HPV infection among college women. - Viscidi, R P (1997)
A human papillomavirus type 16 (HPV-16) virus-like particle (VLP)-based enzyme-linked immunosorbent assay (ELISA) was used to measure serum antibody to capsid proteins in 376 sexually active college women who were also screened for the presence of genital HPVs by PCR and interviewed for demographic and behavioral risk factors for HPV infection. The seroprevalence was 46% in women with HPV-16 DNA in the genital tract. The corresponding values for women who harbored other HPV types or no HPV in the genital tract were 30 and 19%, respectively (HPV-16 group versus no-HPV group; odds ratio [OR], 3.7; 95% confidence interval [CI], 1.5 to 8.9). The antibody response was significantly higher among women with a high viral load than among those with a low viral load (median optical density value, 0.838 versus 0.137, P = 0.009). Comparable levels of seroreactivity were observed among women infected with HPV types distantly or closely related genetically to HPV-16. Seroreactivity was significantly associated with an age of 25 to 30 years (OR, 2.3; 95% CI, 1.2 to 4.4), three or more lifetime sexual partners (OR, 2.9; 95% CI, 1.1 to 10), and history of a sexually transmitted disease other than HPV (OR, 3.1; 95% CI, 1.5 to 6.3). The percent seropositivity increased linearly with number of lifetime sexual partners until reaching a plateau at 35% for women with more than six partners (chi for linear trend, P < 0.001). The low sensitivity of HPV-16 VLP-based ELISA may limit the usefulness of the assay as a diagnostic test for HPV-16 infection. However, the assay appears to have adequate specificity and should be useful as an epidemiological marker of HPV-16 infection and sexual behavior.